When you convert from meters to centimeters, you always multiply by 100, which means that 1 meter = 1 * 100 cm = 100 cm
So, 8.6 meters = 8.6 * 100 cm = 860 cm
Hope this Helps :)
(8,5)(-12,-9)
slope = (-9 - 5) / (-12 - 8) = -14/-20 = 7/10
y = mx + b
slope(m) = 7/10
use either of ur points.....(8,5)....x = 8 and y = 5
now we sub and find b, the y int
5 = 7/10(8) + b
5 = 56/10 + b
5 - 56/10 = b
50/10 - 56/10 = b
-3/5 = b
so ur equation is : y = 7/10x - 3/5.....now we put it in standard form
y = 7/10x - 3/5...multiply by 10
10y = 7x - 6.....subtract 7x
-7x + 10y = -6....multiply by -1
7x - 10y = 6
So.....7x - 10y = 3.... IS NOT a good model. Because ur points are not a solution to ur equation.
Answer:
idk hff 8gciy ctcs 6rxtc igv6rx8
One solution is the answer
Answer:
![F=\frac{-xf+f+2x}{x+1};\quad \:x\ne \:-1](https://tex.z-dn.net/?f=F%3D%5Cfrac%7B-xf%2Bf%2B2x%7D%7Bx%2B1%7D%3B%5Cquad%20%5C%3Ax%5Cne%20%5C%3A-1)
Step-by-step explanation:
![1. \mathrm{Subtract\:}f\left(x+2\right)\mathrm{\:from\:both\:sides}\\ F\left(x+1\right)+f\left(x+2\right)-f\left(x+2\right)=2x+3f-f\left(x+2\right) ](https://tex.z-dn.net/?f=1.%20%5Cmathrm%7BSubtract%5C%3A%7Df%5Cleft%28x%2B2%5Cright%29%5Cmathrm%7B%5C%3Afrom%5C%3Aboth%5C%3Asides%7D%5C%5C%0AF%5Cleft%28x%2B1%5Cright%29%2Bf%5Cleft%28x%2B2%5Cright%29-f%5Cleft%28x%2B2%5Cright%29%3D2x%2B3f-f%5Cleft%28x%2B2%5Cright%29%0A%0A)
![2. \mathrm{Simplify}\\ F\left(x+1\right)=-xf+f+2x\\ ](https://tex.z-dn.net/?f=2.%20%5Cmathrm%7BSimplify%7D%5C%5C%0AF%5Cleft%28x%2B1%5Cright%29%3D-xf%2Bf%2B2x%5C%5C%0A)
![3. \mathrm{Divide\:both\:sides\:by\:}x+1;\quad \:x\ne \:-1\\ \frac{F\left(x+1\right)}{x+1}=-\frac{xf}{x+1}+\frac{f}{x+1}+\frac{2x}{x+1};\quad \:x\ne \:-1](https://tex.z-dn.net/?f=3.%20%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7Dx%2B1%3B%5Cquad%20%5C%3Ax%5Cne%20%5C%3A-1%5C%5C%0A%5Cfrac%7BF%5Cleft%28x%2B1%5Cright%29%7D%7Bx%2B1%7D%3D-%5Cfrac%7Bxf%7D%7Bx%2B1%7D%2B%5Cfrac%7Bf%7D%7Bx%2B1%7D%2B%5Cfrac%7B2x%7D%7Bx%2B1%7D%3B%5Cquad%20%5C%3Ax%5Cne%20%5C%3A-1)
![4. \mathrm{Simplify}\\ F=\frac{-xf+f+2x}{x+1};\quad \:x\ne \:-1](https://tex.z-dn.net/?f=4.%20%5Cmathrm%7BSimplify%7D%5C%5C%0AF%3D%5Cfrac%7B-xf%2Bf%2B2x%7D%7Bx%2B1%7D%3B%5Cquad%20%5C%3Ax%5Cne%20%5C%3A-1)
Final Answer: ![F=\frac{-xf+f+2x}{x+1};\quad \:x\ne \:-1](https://tex.z-dn.net/?f=F%3D%5Cfrac%7B-xf%2Bf%2B2x%7D%7Bx%2B1%7D%3B%5Cquad%20%5C%3Ax%5Cne%20%5C%3A-1)